Hand hygiene practices among health care workers at Nyangabgwe Hospital, Francistown, Botswana - Hlabano, Wazha (My University, 2015)
Background: The purpose of the study was to find out if hand hygiene was being done according to World Health Organization hand hygiene Guideline. It was hoped that the study would benefit all health care workers through making recommendations aimed at improving hand hygiene compliance. Purpose: The aim of the study was to assess hand hygiene practices among healthcare workers in Nyangabgwe Hospital, Francistown, Botswana Methods: Quantitative, Cross-sectional study, using a self-administered Questionnaire to collect data on 280 participants. The questionnaire consisted of three (3) sections: socio-demographic profile; attitudes of HCWs and practice of healthcare on hand hygiene. For attitude questions Three (3) point Likert scale was used. The sampled Healthcare workers were stratified. The results were analysed using SPSS version 24.0. The descriptive statistical method was used to analyse frequencies, correlations and means. The chi-squared was used to analyse cross tabulation between variables and association with significance level at (p < = 0.05). Results: The results shows that 260 participants aged between 20- 60years responded to the questionnaire. The majority of participants had good knowledge of hand hygiene and younger participants practiced hand hygiene more than older ones (p<.05). Barriers to hand hygiene were significant and included lack of time, negative attitude, but not lack of knowledge. Conclusion: The study highlighted the practices of hand hygiene among health care workers and the status of hand hygiene resources in the hospital which have a negative impact on hand hygiene practices demonstrated that compliance with hand hygiene compliance among health care workers remains unacceptably low, despite xiv the irrefutable scientific evidence that hands are the most common vehicle for transmission of pathogens Keywords: Hand hygiene, Health care workers, Hand hygiene practices, Health care associated infection, Resources.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Hand hygiene; Health care workers; Hand hygiene practices; Hand -- Care and hygiene -- Botswana -- Francistown; Hospitals -- Sanitation; Health care teams -- Botswana -- Francistown; Hand washing